Implementation of Response Surface Methodology for Enhanced Production of Endoglucanase by Thermophilic Aspergillus Fumigatus - Sufia Tazeen; Mahmood, Raja Tahir; Asad, Muhammad Javaid; Zafar, Mudassar Zafar; Abbasi, Ansar Ahmed; Hameed, Khalid; Nisar, Rameez (BioScientific Review, 2021)
Enzymes are biocatalysts which play key roles in the body of living organisms. Cellulose is major source of plant biomass. Its β-1,4-glucosidic bonds are hydrolyzed by cellulases. These cellulases can be produced by a variety of microorganisms including fungi, bacteria and actinomycetes which are used today for the industrial applications. The current study was aimed to optimize the cultural conditions for maximum production of endoglucanase by Aspergillus fumigatus through solid state fermentation of sugarcane bagasse. Response Surface Methodology (RSM) was employed under Central Composite Design (CCD) for the optimization of growth including pH, temperature, time period & inoculum size and nutritional parameters including glucose, fructose and (NH₄)₂SO₄. The effect of different metal ions on endoglucanase production was also monitored. It was partially purified by (NH₄)₂SO₄ precipitation and gel filtration chromatography. Finally, edogucanase was characterized for optimum pH, temperature and determination of kinetic parameters. Maximum enzyme activity was found as 0.9 IU/mL/min in the presence of 6 g substrate, 3.5 mL inoculum, 4.5 pH, 40 °C temperature at incubation time of 84 hrs. After addition of carbon and nitrogen sources enzyme activity increased to 1.4 IU/mL/min. It was further increased to 1.56 IU/mL/min with 0.42% of CaCl2. Maximum purification was achieved at 50% saturation by ammonium sulphate (NH₄)₂SO₄. Optimum temperature and pH were 40 °C and 5 respectively, whereas the values for Km and Vmax were 5.37 mM and 696 uM/mL/min., respectively. These findings suggested that endoglucanase by Aspergillus fumigatus could be suitable for various industries. Keywords: Aspergillus fumigatus, Central Composite Design (CCD), endoglucanase, Response Surface Methodology (RSM), Solid State Fermentation (SSF) Copyright (c) The Authors